Portrait Of Arabic Language Immersion Program In Indonesian Islamic Colleges - Musthofa, Tulus; Rosyadi, Faiq Ilham; Yusuf, Muhammad (Ijaz Arabi Journal of Arabic Learning, 2025)
The discourse of language immersion is the antithesis of the language environment, which has been considered the ideal endeavor in Arabic language pedagogy in Islamic universities in Indonesia. In contrast to the language environment, which requires community instruments to optimize Arabic, language immersion looks more from the perspective of the quantity and quality of students interacting with Arabic. This paper examines the description of the Arabic language immersion program in Islamic universities in Indonesia. This paper is in the form of a case study. The author chose Islamic universities in the Yogyakarta area as the object of research, namely: Muhammadiyah University of Yogyakarta, Sunan Kalijaga State Islamic University, Ahmad Dahlan University, and Pandanaran Islamic College. Data collection used questionnaires, interviews, and documentation; data analysis borrowed from the Miles and Huberman procedure. The study results indicate that Arabic language immersion programs in Islamic universities in Indonesia universally use an artificial immersion basis to provide students with Arabic language knowledge and skills to form communication competencies like those in Arab society. The immersion model with the most significant percentage of use is the partial immersion model. The methods used are qowaid wa tarjamah, direct method, audio lingual-visual method, communicative method, and eclectic method. Meanwhile, the effectiveness and efficiency of the immersion program will be evaluated using test and non-test methods.